Green valley galaxies as a transition population in different environments - Coenda, Valeria (2018)
We present a comparative analysis of the properties of passive, star-forming and transition (green valley) galaxies in four discrete environments: field, groups, the outskirts and the core of X-ray clusters. We construct samples of galaxies from the Sloan Digital Sky Survey in these environments so that they are bound to have similar redshift distributions. The classification of galaxies into the three sequences is based on theUV-optical colourNUV-r. We study a number of galaxy properties: stellar mass, morphology, specific star formation rate and the history of star formation. The analysis of green valley (GV) galaxies reveals that the physical mechanisms responsible for external quenching become more efficient moving from the field to denser environments. We confirm previous findings thatGVgalaxies have intermediate morphologies; moreover, we find that this appears to be independent of the environment. Regarding the stellar mass of GV galaxies, we find that they tend to be more massive in the field than in denser environments. On average, GV galaxies account for ~20 per cent of all galaxies in groups and X-ray clusters. We find evidence that the field environment is inefficient in transforming lowmass galaxies. GV galaxies have average star formation histories intermediate between passive and star-forming galaxies, and have a clear and consistent dependence on the environment: both, the quenching time and the amplitude of the star formation rate, decrease towards higher density environments.